2006
DOI: 10.1007/s10346-005-0027-7
|View full text |Cite
|
Sign up to set email alerts
|

Extremely large rockslides and rock avalanches in the Tien Shan Mountains, Kyrgyzstan

Abstract: Most systematic research on large rock-slope failures is geographically biased towards reports from Europe, the Americas, the Himalayas and China. Although reports exist on large rockslides and rock avalanches in the territory of the former Soviet Union, they are not readily available, and few translations have been made. To begin closing this gap, we describe here preliminary data from field reconnaissance, remote sensing and geomorphometry of nine extremely large rock-slope failures in the Tien Shan Mountain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(77 citation statements)
references
References 21 publications
2
75
0
Order By: Relevance
“…3). It has an estimated volume of 5-6 km 3 (and may be even more than 6 km 3 according to Strom and Korup, 2006). This volume is only exceeded by the already breached rockslide dam of Beshkiol rockslide located in the south-east of zone Z1.…”
Section: Landslide Types: Giant Landslides and Natural Damsmentioning
confidence: 97%
See 1 more Smart Citation
“…3). It has an estimated volume of 5-6 km 3 (and may be even more than 6 km 3 according to Strom and Korup, 2006). This volume is only exceeded by the already breached rockslide dam of Beshkiol rockslide located in the south-east of zone Z1.…”
Section: Landslide Types: Giant Landslides and Natural Damsmentioning
confidence: 97%
“…The landslide inventory was compiled from various digital maps of rockslides produced by the authors (see, e.g., Strom and Korup, 2006, for a description of the largest identified rockslides) as well as landslide maps created in the frame of Master's Theses completed at the University of Liege, Belgium (Schlögel, 2009;Dupont, 2011;Burette, 2012). Additionally, more than 1800 other landslides have been mapped recently in soft sediments (around the Fergana Basin and along the southern border of the Tien Shan, see landslides outlined in yellow near the zones Z3, Z4, Z5 in Fig.…”
Section: Tien Shan Geohazards Database: Landslidesmentioning
confidence: 99%
“…Most of the case studies identified in this area were described in Abdrakhmnatov and Strom (2006), Hartvich et al (2008), Strom (1994Strom ( , 1996Strom ( , 2006Strom ( , 2010Strom ( , 2013aStrom ( , b, c, d, 2015, Strom and Groshev (2009), Strom and Korup (2006), Strom and Stepanchikova (2008), and Strom and Zhirkevich (2013).…”
Section: Rockslides In the Kokomeren River Basinmentioning
confidence: 99%
“…The first documented observations of slope instabilities in this region date to the end of the 19th century (Ignatiev 1886). However, several of these mass movements were neither documented nor did they cause significant damages, since they occurred in remote and sparsely inhabited areas (Strom and Korup 2006).…”
Section: Study Regionmentioning
confidence: 99%